PERHITUNGAN HARGA POKOK PENJUALAN DALAM MENINGKATKAN LABA PADA REGINA FLORIST MEDAN - Rismala Nova Angelia Hutagaol; Zulia Rifda Daulay (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Regina Florist is one of the small and medium industries that is currently widely available. Florist is a term commonly used for the professional flower trade. A florist has duties and responsibilities for the design and creation of flower arrangements. In this reseach, it turns out that Regina Florist is businnes has not calculated the cost of goods sold for the businnes is founded, because the businnes owner does not know how to calculate the of good sold, even though the benefit of calculating COGS is to know accurately how much it cost to produce a product and its function. COGS is so that sellers can know what the basic price is and how much the goods cost in order to make a profit. Profit is the net income obtained by a company by subtracting all cost from gross income. Based on these problems, researchers are interested in conducting reseach on “ Cost of Goods Sold in Increasing Profits at Regina Florist Medan”. The method used in this research is a qualitative method, namely using interview results and observation results as data collection tools. Then the aim of this research is to find out the types of cost that are calculated in calculating the cost of goods sold and to find out how to increase profits at Regina Florist Medan.